The role of government in Singapore’s economic development - Akylbay, A. (Journal of Oriental Studies, 2022)
This article discusses some theoretical conceptual aspects of public administration in Singapore. Compared to other fast-growing Asian economies, the way the Singapore government intervenes in the economy is both large and intrusive, but less attention is paid to GDP growth and surplus accumulation as the main goals. The ruling government’s complete dominance in politics allowed it to mobilize resources to create prerequisites for strong GDP growth and high savings. This article analyzes how government intervention affects the evolution of Singapore’s economy, as well as its successes and failures. It is shown how a pragmatic approach helped overcome the difficulties faced by Singapore at the initial stage of economic development. The article scientifically explains how a pragmatic approach was used to restructure the economy in the early 2000s, so that innovation took a central place as a driving force for growth. The content of the article also discusses the problems that led to a pragmatic approach to managing a growth-oriented economy, and what this means for the future of the economy. Key words: Singapore, government, public administration, economic development, development model.